Malignant transformation of oral leukoplakia and oral lichen planus: a retrospective cohort study of 293 Ukrainian patients - Yuliia Kolenko (Kazimierz Wielki University, 2017)
Background: The five-year survival rate of early stage (I and II) oral squamous cell carcinoma might be about 80%, but of advanced stage (III and IV) oral squamous cell carcinoma is only approximately 20%. Because most cases of oral squamous cell carcinoma are preceded by clinically evident oral potentially malignant disorders, it is important to prevent malignant change for those patients diagnosed with oral potentially malignant disorders. Purpose: to estimate the malignant transformation rate of a retrospective cohort of 293 patients with oral leukoplakia (OL) and oral lichen planus (OLP) (mean follow-up of 4,5 years) and identify significant risk factors of malignant transformation in Ukraine. Materials and Methods: All archived files of patients with the clinical and pathologic diagnosis of OL and OLP from 2011 to 2015 were retrospectively reviewed in Oncology Hospital in Zhitomir and Chernigov. All clinical history and follow-up data were obtained from the archived files. Information regarding gender, age, site of lesions at the time of the initial diagnosis of OL and OLP was all documented in detail. Results: Two important parameters should be considered when evaluating the potential for malignant transformation of OPMDs. First, the initial OPMD lesions should be confirmed using histopathological diagnoses; second, the amount of time it takes for the lesion to be transformed into a malignancy at the same location as the original OPMD lesion. Conclusions: In the current study, we analyzed and updated the data of malignant transformation of various OPMDs in a cohort of patients from Ukraine. Moreover, our data indicated that patients with OPMDs need a long-term clinical follow-up and histopathological examination is an important predictor of cancer development to monitor the possibility of malignant transformation.